Relationships between the El Niño–Southern Oscillation, precipitation, and nitrogen wet deposition rates in the contiguous United States. Issue 11 (21st November 2016) - Nergui, Tsengel; Evans, R. David; Adam, Jennifer C.; Chung, Serena H.
Abstract: Human activities have significantly increased reactive nitrogen (N) in the environment, leading to adverse effects on various ecosystems. We used 1979–2012 seasonal inorganic N wet deposition data from the National Atmospheric Deposition Program to evaluate the relationship between the El Niño–Southern Oscillation (ENSO) and N wet deposition in the contiguous U.S. The correlations between precipitation and inorganic N wet deposition were the strongest and most spatially extensive during winter; up to 62% and 53% of the 2 to 6 year variations of precipitation and N wet deposition rates, respectively, in the Rocky Mountains, along the coast of the Gulf of Mexico and near the Great Lakes, can be explained by variation in the NINO3.4 climate index, which was used as a measure of ENSO activity. During El Niño winters, precipitation and N wet deposition rates were higher than normal in the southern U.S., while La Niña events brought higher precipitation and N wet deposition to the Rocky Mountains and Great Lakes regions. Wintertime N wet deposition correlations held through springtime in the Great Lakes and the northeast; however, correlations between NINO3.4 and precipitation were not significant at most sites, suggesting factors besides precipitation amount contributed to the 2 to 6 year variation of N wet deposition in these regions. As the frequency, strength, and types of ENSO change in the future, interannual variability of N wet deposition will be affected, indirectly affecting spatial distribution of dry N deposition and potentially changing the overall spatial patterns of N deposition. Key Points: Relationship between NINO3.4 and nitrogen (N) wet deposition in the U.S. was investigated using wavelet analysis Wintertime N wet deposition in the Rock Mountains, Great Lakes, and Gulf regions were correlated with ENSO Factors other than precipitation drove springtime correlations between N wet deposition and ENSO in the Great Lakes and the northeast